Real estate application development and recommendations (III) - Tan, Jolene (Nanyang Technological University, 2023)
Selecting a property is a fundamentally challenging decision that involves not only navigating the complexities of the real estate market, but also weighing multiple user criteria and decision factors. To address these challenges and demonstrate the potential of technology to transform and improve the real estate industry, a cross-platform application, PropNex Investment Suite was proposed to be developed. This application not only offers users an intuitive user interface, but also a plethora of features and tools that aim to help property seekers ease their decision-making process, the most notable one being the item-based recommendation system. Recommendation systems recommend products to customers and have gained immense popularity from recent times, becoming important commercial enterprise tools. The application’s frontend is developed using the cross-platform framework Ionic-Angular that supports both web and mobile (iOS and Android) platforms. The backend consists of the Firebase Realtime Database. The recommendation system returns the top 3 most similar properties to the one in focus and is implemented using the k-nearest neighbour algorithm with euclidean distance as the defined similarity metric.